(untitled) - Zander, Michael (Oxford, 2015)
As a critical analysis of the law-making process, this book has no equal. For more than three decades it has filled a gap in the requirements of students in law or political science taking introductory courses on the legal system and is now in its 7th edition. It deals with every aspect of the law-making process: the preparation of legislation; its passage through Parliament; statutory interpretation; binding precedent; how precedent works; law reporting; the nature of the judicial role; European Union law; and the process of law reform.
Keywords: Legislation,Luật; Great Britain,Vương quốc Anh